The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1111/j.1365-313x.2007.03098.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple loss‐of‐function of Arabidopsis gibberellin receptor AtGID1s completely shuts down a gibberellin signal

Abstract: SummaryArabidopsis carries three receptor genes for the phytohormone gibberellin (GA), AtGID1a, AtGID1b and AtGID1c. Expression of each gene in the rice gid1-1 mutant for GA receptors causes reversion of its severely dwarfed phenotype and GA insensitivity to a normal level, even though each loss-of-function mutant shows no clear phenotype in Arabidopsis (Nakajima et al., 2006). In this paper, we report the functional redundancy and specificity of each AtGID1 by analyzing the multiple mutants for loss of functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
104
0
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 24 publications
4
104
0
12
Order By: Relevance
“…The triple mutant gid1a gid1b gid1c in Arabidopsis is a nongerminating extreme dwarf, whose phenotype is even more severe than the GA-deficient ga1-3 mutant ( Figure 7B; Griffiths et al, 2006;Iuchi et al, 2007;Willige et al, 2007). As expected, this triple mutant is impaired in flower initiation.…”
Section: Gid1ssupporting
confidence: 60%
“…The triple mutant gid1a gid1b gid1c in Arabidopsis is a nongerminating extreme dwarf, whose phenotype is even more severe than the GA-deficient ga1-3 mutant ( Figure 7B; Griffiths et al, 2006;Iuchi et al, 2007;Willige et al, 2007). As expected, this triple mutant is impaired in flower initiation.…”
Section: Gid1ssupporting
confidence: 60%
“…While rice possesses only a single GID1 gene, there are three Arabidopsis genes homologous to rice GID1. Nakajima et al (2006) confirmed that the products of these Arabidopsis genes also interact with active GAs, and Griffiths et al (2006), Willige et al (2007), and Iuchi et al (2007) showed that the Arabidopsis triple mutant gid1a gid1b gid1c results in a severe GA-insensitive dwarf phenotype. Based on the results of functional and biochemical analyses of these three GA signaling factors, the following molecular mechanism of GA perception has been proposed (Ueguchi-Tanaka et al, 2007b;Hirano et al, 2008).…”
Section: Introductionmentioning
confidence: 74%
“…The significance of GA metabolic genes in germination can be seen in the altered germination frequencies of GA metabolic mutants, such as ga requiring1 (ga1), ga2, ga3, ga4, ga5, and ga2ox2 (Koornneef and Van der Veen, 1980;Talon et al, 1990;Sun et al, 1992;Sun and Kamiya, 1994;Xu et al, 1995;Williams et al, 1998;Yamauchi et al, 2007). Light-induced increase in GA leads to the degradation of DELLA proteins via SCF SLY1 ubiquitin E3 ligase in conjunction with GA receptors (GA INSENSITIVE DWARF 1a [GID1a], -1b, and -1c) (Itoh et al, 2003;McGinnis et al, 2003;Dill et al, 2004;Ueguchi-Tanaka et al, 2005Griffiths et al, 2006;Iuchi et al, 2007;Jiang and Fu, 2007). DELLA proteins are nucleus-localized negative GA signaling components that inhibit various GA responses, including seed germination, stem elongation, and floral development (Peng et al, 1997(Peng et al, , 1999Silverstone et al, 1998;Ikeda et al, 2001;Sun and Gubler, 2004;Tyler et al, 2004).…”
Section: Introductionmentioning
confidence: 99%